RPHC4 Thematic Report: Characteristics of Households and Housing - National Institute of Statistics of Rwanda. (2014)

KEY FIGURES: 5th Rwanda Population and Housing Census (PHC) - National Institute of Statistics of Rwanda. (National Institute of Statistics of Rwanda., 2023)
The fifth Population and Housing Census in Rwanda, was conducted in August 2022. The Census operation was coordinated by the National Census Commission. Various census technical and administrative structures have been put in place to ensure a successful census operation.

Fourth Population and Housing Census, Rwanda, 2012: Thematic Report: Characteristics of Households and Housing - National Institute of Statistics of Rwanda (NISR) (Ministry of Finance and Economic Planning (MINECOFIN), 2012)